Method validation and antioxidant activities of Hyperacanthus amoenus and Carissa bispinosa - Kedibone G. Kgosana; Tirelo Matlala (Onderstepoort Journal of Veterinary Research)
Plant foliages used as feed additives pose a health risk due to high oxidant concentrations. Oxidants cause oxidative stress and high rate of morbidities and mortalities. Hence, the aim of the study was to validate the methods to quantify gallic acid (GA) and quercetin (Q) as putative antioxidants, and to evaluate antioxidant activities in feed (F), Hyperacanthus amoenus (HA) and Carissa bispinosa (CB) extracts. Extraction was carried out with 62.5% methanol. Method validations for linearity, accuracy and precision were performed on high performance liquid chromatography. Quantitative analysis of GA and Q and testing of 2,2-diphenyl-2-picrylhydrazyl (DPPH) scavenging activities in the extracts were performed. The lowest limit of detection (LOD) and limit of quantitation (LOQ) of 0.011 µg/mL and 0.032 µg/mL were determined in HA, respectively. The methods were accurate and precise as the relative standard deviations (%RSD) were less than 15%. The GA concentrations in CB and HA extracts were statistically significant (p  0.05) and their values were 0.65 ± 0.03 x 106 µg/kg dry weight (DW) (0.13%) and 0.28 ± 0.06 x 106 µg/kg DW (0.002%), respectively. All extracts showed very strong radical scavenging activities with their IC50 values ranging between 5.87 µg/mL and 6.86 µg/mL.